PENERAPAN AJARAN TRI PARARTHA DALAM MEMBENTUK KARAKTER SISWA DI SMP NEGERI 12 DENPASAR - Dewa Ayu, I Dewa Ayu Setiyawati; Arini, Ni Wayan; Mardika, I Made Nasib (UHN IGB Sugriwa Denpasar, 2024)
Character education is the basis for forming ethics in children's personalities, especially students at SMP Negeri 12 Denpasar. Thus, one of the teachings used to shape students' character is through the Tri Parartha Teaching. Tri Parartha are three teachings that can shape a child's character, namely Asih, Punia and Bhakti. The formulation of the problem discussed in this research is as follows: (1) What is the form of application of the Tri Parartha teachings in shaping student character at SMP Negeri 12 Denpasar? (2) What are the characters that are formed from the application of the Tri Parartha teachings in shaping the character of students at SMP Negeri 12 Denpasar? (3) What are the obstacles and efforts made in implementing the Tri Parartha teachings in shaping student character at SMP Negeri 12 Denpasar? The results obtained in this research are: (1) the form of application of the Tri Parartha teachings, namely caring for others (compassion), providing emotional support to friends, caring for the environment, praying sincerely, being an alert ambassador (loving and looking after), sharing, saying hello. and greet the teacher, and perform prayers together. (2) character formed from the application of the Tri Parartha teachings, namely faith and devotion to God Almighty, global diversity, mutual cooperation, independence, critical reasoning and creativity. (3) obstacles in implementing the Tri Parartha teachings, namely the different characters of students, social media, students' economic factors, the application of Bhakti teachings is not optimal. (4) Efforts made to overcome problems in implementing the Tri Parartha teachings are providing understanding and approaches to students, using gadgets wisely, increasing students' awareness by providing sincere assistance, increasing the role of teachers in maximizing the application of bhakti teachings. Keywords: Teachings of Tri Parartha, student character